2016
DOI: 10.1159/000455042
|View full text |Cite
|
Sign up to set email alerts
|

Superiority in Quality of Life Improvement of Biologics over Conventional Systemic Drugs in a Swiss Real-Life Psoriasis Registry

Abstract: Background: Randomized controlled trials have shown the efficacy of systemic treatments in moderate-to-severe psoriasis. Clinical outcomes in psoriasis patients under real-world conditions are less well understood. Objective: This study compared Psoriasis Area and Severity Index (PASI) and Dermatological Life Quality Index (DLQI) improvement in all psoriasis patients registered in the Swiss Dermatology Network for Targeted Therapies. We asked whether outcomes differed between 4 treatment strategies, namely bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
2
17
0
2
Order By: Relevance
“…In our data set, the mean age of patients was 47 years, with a predominance of men, overweight patients and smokers (50%) and with 23% of patients presenting PsA. These characteristics were in‐line with previous reports from the SDNTT registry and results from pooled analyses of other national registries …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our data set, the mean age of patients was 47 years, with a predominance of men, overweight patients and smokers (50%) and with 23% of patients presenting PsA. These characteristics were in‐line with previous reports from the SDNTT registry and results from pooled analyses of other national registries …”
Section: Discussionsupporting
confidence: 88%
“…This was a retrospective analysis of baseline data collected within the SDNTT registry between March 2011 and December 2017 . All patients gave written informed consent before inclusion in the registry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hair follicle is considered ‘immune privileged’ as, at certain times in the hair cycle, it can protect itself from immune recognition and inflammatory responses via a loss of major histocompatibility complex class I and II expression, and by expressing CD200, α‐melanocyte‐stimulating hormone, TGF‐β2, macrophage migration inhibitory factor and indoleamine‐2,3‐dioxygenase . The role of TGF‐β2 may be especially interesting because a confirmed genome‐wide significant signal was found close by in patients with acne, and the authors also found TGF‐β2 to be downregulated in fresh acne biopsies …”
Section: Pathogenesismentioning
confidence: 97%
“…131,135 The role of TGF-b2 may be especially interesting because a confirmed genome-wide significant signal was found close by in patients with acne, and the authors also found TGF-b2 to be downregulated in fresh acne biopsies. 136 Multiple immune cells, including Langerhans cells, T cells (CD4 + and CD8 + ), macrophages and mast cells are commonly located in and around the hair follicle. 135 Langerhans cells have been a particular focus of recent study.…”
Section: Aberrant Immune Responsesmentioning
confidence: 99%